Cannot rewrite goal with assertion? - coq

I am not sure I understand why in some cases rewriting H works, and in some it doesnt.
Here for example:
Theorem add_assoc2 : forall n m: nat, n + m = m + n.
Proof. intros. rewrite add_comm. reflexivity. Qed.
Theorem plus_4: forall n m p q: nat,
n + (n * p) + m + (m * p) = n + m + (n * p) + (m * p).
Proof.
intros.
assert (H: n * p + m = m + n * p).
{ rewrite <- add_assoc2. reflexivity. }
rewrite H.
Gives:
1 goal
n, m, p, q : nat
H : n * p + m = m + n * p
______________________________________(1/1)
n + n * p + m + m * p = n + m + n * p + m * p
But Coq complains: Found no subterm matching "n * p + m" in the current goal.
Why?
I clearly see one, on the left side. When using induction, rewriting with IHn doesn't pose any problem, even if there are some other terms in front of rewriteable expression.

You can "see" a subterm n * p + m, but this is misleading: Coq doesn't show you the implicit parentheses around all the + expressions.
Use
Set Printing Parentheses.
to make them visible. Your proof state is really:
n, m, p, q : nat
H : ((n * p) + m) = (m + (n * p))
============================
(((n + (n * p)) + m) + (m * p)) = (((n + m) + (n * p)) + (m * p))
Coq was right that there is no subterm that matches H's left hand side expression ((n * p) + m). You need to rewrite using some associativity lemmas to shift the parentheses around.
Also, add_assoc2 is not a good name for a lemma forall n m: nat, n + m = m + n. This is a commutativity property, not associativity.

Related

How to prove a*b*c=a*(b*c) in Coq?

Im trying to prove the above question. I have been given a definition of an induction:
Definition nat_ind
(p : nat -> Prop)
(basis : p 0)
(step : forall n, p n -> p (S n)) :
forall n, p n := fix f n :=
match n return p n with
| 0 => basis
| S n => step n (f n)
end.
This is my attempt, but don't know how to finish
Goal forall a b c, a * b * c = a * (b * c).
Proof.
apply nat_ind.
- intros a b c. revert a.
apply (nat_ind (fun a => a * b * c = a * (b * c))); simpl.
+ reflexivity.
+ intros. f_equal. intros.
After your very first nat_ind invocation, if you look at your goal, you see that Coq did not do the right thing at all!
______________________________________(1/3)
forall a b c : nat, a * b * c = a * (b * c)
______________________________________(2/3)
nat ->
(forall a b c : nat, a * b * c = a * (b * c)) ->
forall a b c : nat, a * b * c = a * (b * c)
______________________________________(3/3)
nat
What happened here is that it made a guess for your motive p, and decided to unify it with fun (_ : nat) => <YOUR_WHOLE_GOAL>, a function which given any nat would give your goal... Yes, this is silly!
One way to nudge it into doing the induction on a is by explicitly forcing it to do so, with:
apply nat_ind with (n := a)
(where the n matches the name used in your definition of nat_ind)
After this, you get the much more reasonable goals:
______________________________________(1/2)
forall b c : nat, 0 * b * c = 0 * (b * c)
______________________________________(2/2)
forall n : nat,
(forall b c : nat, n * b * c = n * (b * c)) ->
forall b c : nat, S n * b * c = S n * (b * c)
where indeed a has been replaced by 0 and S n respectively.
[EDIT: I guess this does not quite answer your question as you had gotten your way to the same point with the second induction call...]
To solve your goal, it will help a lot to have a property about distributivity of multiplication over addition:
forall n m p, (n + m) * p = n * p + m * p
All of these, as well as what you're trying to prove, already exists in Coq. Is this homework? Are you just training?

How to show injectivity of a function?

Here's what I'm trying to prove: Theorem add_n_injective : forall n m p, n + m = n + p -> m = p.
The + is notation for plus, defined as in https://softwarefoundations.cis.upenn.edu/lf-current/Basics.html:
Fixpoint plus (n : nat) (m : nat) : nat :=
match n with
| O ⇒ m
| S n' ⇒ S (plus n' m)
end.
In Agda, one can do cong (n + _) to use the fact that n + m = n + p for any n m p.
Coq's built-in tactices injection and congruence both seemed promising, but they only work for constructors.
I tried the following strategy and kept hitting weird errors or getting stuck:
make an inductive type for bundling up a proof of (n + m = s): Sum (n m s)
use the congruence tactic in a lemma that shows Sum (n m s) = Sum (n p s)
use constructing Sums, destruct, and the lemma to show that n + m = n + p
Is there an easier way to prove this? I feel like there must be some built-in tactic I'm missing or some trickery with unfold.
UPDATE
Got it:
Theorem add_n_injective : forall n m p, n + m = n + p -> m = p.
Proof.
intros. induction n.
- exact H.
- apply IHn. (* goal: n + m = n + p *)
simpl in H. (* H: S (n + m) = S (n + p) *)
congruence.
Qed.
Thanks #ejgallego
Injectivity of plus is not an "elementary" statement, given that the plus function could be arbitrary (and non-injective)
I'd say the standard proof does require induction on the left argument, indeed using this method the proof quickly follows.
You will need injection when you arrive to a goal of the form S (n + m) = S (n + p) to derive the inner equality.

even (n + m) -> even n /\ even m \/ odd n /\ odd m

How can I prove this lemma:
Lemma even_plus_split n m :
even (n + m) -> even n /\ even m \/ odd n /\ odd m.
These are the only libraries and definition that can be used:
Require Import Arith.
Require Import Coq.omega.Omega.
Definition even (n: nat) := exists k, n = 2 * k.
Definition odd (n: nat) := exists k, n = 2 * k + 1.
I am new to Coq and confused about it. Can you give me a solution? Thanks in advance!
the code so far:
Lemma even_plus_split n m :
even (n + m) -> even n /\ even m \/ odd n /\ odd m.
Proof.
intros.
unfold even.
unfold even in H.
destruct H as [k H].
unfold odd.
exists (1/2*k).
result so far:
1 subgoal
n, m, k : nat
H : n + m = 2 * k
______________________________________(1/1)
(exists k0 : nat, n = 2 * k0) /\ (exists k0 : nat, m = 2 * k0) \/
(exists k0 : nat, n = 2 * k0 + 1) /\ (exists k0 : nat, m = 2 * k0 + 1)
I just want to make k0 equals to 1/2*k, and therefore I suppose it would make sense, but I can't do that.
I just want to make k0 equals to 1/2*k, and therefore I suppose it would make sense, but I can't do that.
There is a function called Nat.div2, which divides a natural number by 2. Running Search Nat.div2.
Nat.le_div2: forall n : nat, Nat.div2 (S n) <= n
Nat.lt_div2: forall n : nat, 0 < n -> Nat.div2 n < n
Nat.div2_decr: forall a n : nat, a <= S n -> Nat.div2 a <= n
Nat.div2_wd: Morphisms.Proper (Morphisms.respectful eq eq) Nat.div2
Nat.div2_spec: forall a : nat, Nat.div2 a = Nat.shiftr a 1
Nnat.N2Nat.inj_div2: forall a : N, N.to_nat (N.div2 a) = Nat.div2 (N.to_nat a)
Nnat.Nat2N.inj_div2: forall n : nat, N.of_nat (Nat.div2 n) = N.div2 (N.of_nat n)
Nat.div2_double: forall n : nat, Nat.div2 (2 * n) = n
Nat.div2_div: forall a : nat, Nat.div2 a = a / 2
Nat.div2_succ_double: forall n : nat, Nat.div2 (S (2 * n)) = n
Nat.div2_odd: forall a : nat, a = 2 * Nat.div2 a + Nat.b2n (Nat.odd a)
Nat.div2_bitwise:
forall (op : bool -> bool -> bool) (n a b : nat),
Nat.div2 (Nat.bitwise op (S n) a b) = Nat.bitwise op n (Nat.div2 a) (Nat.div2 b)
Of these, the most promising seems to be Nat.div2_odd: forall a : nat, a = 2 * Nat.div2 a + Nat.b2n (Nat.odd a). If you pose proof this lemma, you can destruct (Nat.odd a) and use simpl to get that either a = 2 * Nat.div2 a or a = 2 * Nat.div2 a + 1, for whichever a you choose.
This may not give you a solution directly (I am not convinced that setting k0 to k / 2 is the right decision), but if it does not, you should make sure that you can figure out how to prove this fact on paper before you try it in Coq. Coq is very good at making sure that you don't make any jumps of logic that you're not allowed to make; it's extremely bad at helping you figure out how to prove a fact that you don't yet know how to prove.
Everybody who tries to answer seems to be dancing around the fact that you actually chose a wrong direction for this proof. Here is a example:
if n = 601 and m = 399, then n + m = 2 * 500,
n = 2 * 300 + 1, and m = 2 * 199 + 1.
Between 500, 300, and 199, the 1/2 ratio does not appear anywhere.
Still the statement (even n /\ even m) / (odd n /\ odd m) is definitely true.
So for now, you have more a math problem than a Coq problem.
You have to make a proof for universally quantified numbers n and m, but somehow this proof should also work for specific choices of these numbers. So in a sense you can make the mental exercise of testing your proof on examples.

How do I prove the simplified Chinese Remainder Theorem?

I've managed to prove
Theorem modulo_inv : forall m n : Z, rel_prime m n -> exists x : Z, (m * x == 1 [n]). Admitted.
My question is how to finish the following proof (maybe using the modulo_inv theorem?):
Variables m n : Z.
Hypothesis co_prime : rel_prime m n.
Theorem SimpleChineseRemainder :
forall a b : Z, exists x : Z, (x == a [m]) /\ (x == b [n]).
Here is what I tried, but I don't know whether it is correct or not.
Proof.
intros a b.
exists ((a * n) * (n ^ (-1) mod m) + (b * m) * (m ^ (-1) mod n)).
refine (conj _ _).
(* case : ((a * n) * (n ^ (-1) mod m) + (b * m) * (m ^ (-1) mod n) == a [m]) *)
red.
rewrite Z.add_sub_swap.
apply Z.divide_add_r.
(* case : ((a * n) * (n ^ (-1) mod m) + (b * m) * (m ^ (-1) mod n) == b [n]) *)
Can anybody provide any suggestions?
Code-golfing Anton's answer, I was hoping that ring would be clever enough to use the Eq information, and that the proof would simply be
Theorem SimpleChineseRemainder' a b : exists x : Z, (x == a [m]) /\ (x == b [n]).
Proof.
destruct (rel_prime_bezout _ _ co_prime) as [u v Eq];
exists (a * v * n + b * u * m); split ; [ exists ((b-a)*u) | exists ((a-b)*v)]; ring.
Qed.
Unfortunately it didn't automatically exploit that u * m + v * n = 1 -> u * m = 1 - v * n. So until we have a stronger tactic, I guess that has to be added manually, like so:
Theorem SimpleChineseRemainder' a b : exists x : Z, (x == a [m]) /\ (x == b [n]).
Proof.
destruct (rel_prime_bezout _ _ co_prime) as [u v Eq].
exists (a * (v * n) + b * (u * m)); split ; [ exists ((b-a)*u) | exists ((a-b)*v)].
- replace (v*n) with (1-u*m) by (rewrite <- Eq; ring); ring.
- replace (u*m) with (1-v*n) by (rewrite <- Eq; ring); ring.
Qed.
EDIT: The nsatz tactic is able to solve the equation system. However, it introduces a notation for [ ... ] that conflicts with the notation introduced above, and I don't know how to handle that. However, by changing the notation to i.e. [[ ... ]], the proof becomes just two lines:
Require Import Nsatz.
Theorem SimpleChineseRemainder' a b :
exists x : Z, (x == a [[m]]) /\ (x == b [[n]]).
Proof.
destruct (rel_prime_bezout _ _ co_prime) as [u v Eq];
exists (a * v * n + b * u * m); split ; [ exists ((b-a)*u) | exists ((a-b)*v)]; nsatz.
Qed.
Reusing the proof from Wikipedia which is based on Bézout's lemma, we get the following:
From Coq Require Import ZArith Znumtheory.
Import Z.
Definition modulo (a b n : Z) : Prop := (n | (a - b)).
Notation "a == b [ n ]" := (modulo a b n) (at level 50).
Section SimpleChineseRemainder.
Variables m n : Z.
Hypothesis co_prime : rel_prime m n.
Theorem SimpleChineseRemainder a b : exists x : Z, (x == a [[m]]) /\ (x == b [[n]]).
Proof.
destruct (rel_prime_bezout _ _ co_prime) as [u v Eq].
exists (a * v * n + b * u * m); split; [| rewrite add_comm in *];
match goal with |- _ == ?c [_] => replace c with (c * 1) at 2 by apply mul_1_r end;
rewrite <-Eq, mul_add_distr_l, !mul_assoc;
now eexists; rewrite add_add_simpl_l_r, <-mul_sub_distr_r.
Qed.
End SimpleChineseRemainder.

Why is following Coq rewrite not applying on right hand side of assumption?

I have following Coq env.
1 subgoals
m : nat
IHm : forall n : nat, n + n = m + m -> n = m
n : nat
H : S (n + S n) = S (m + S m)
ll := ll : forall k : nat, k + S k = S k + k
Doing rewrite ll in H, only changes the LHS S (n + S n) to S (S n + n) but not the RHS S (m + S m). ll should be applicable on all variables of type nat. What is wrong here?
Expanding on Emilio's comment, rewrite H and rewrite H in H' will first find an instantiation for all (dependently) quantified variables of H, and then replace all occurrences* of that instantiated LHS with the RHS. I believe it finds the topmost/leftmost instantiation in the syntax tree. So, for example, if you do this:
Goal forall a b, (forall x, x + 0 = x) -> (a + 0) * (a + 0) * (b + 0) = a * a * b.
intros a b H.
rewrite H.
the rewrite H will choose to instantiate x with a, and the resulting goal will be a * a * (b + 0) = a * a * b. You can prefix the lemma with ! (as in rewrite !H) to mean "rewrite everywhere, picking as many instantiations as you can", or with ? (as in rewrite ?H) to mean try rewrite !H, i.e., you can pick multiple instantiations, and also don't fail if you can't find any.
*There's actually a bit more nuance, which is that the replacement is done in a single pass with rewrite H and in multiple passes with rewrite ?H and rewrite !H. This only shows up when the first replacement(s) expose other replacement locations that weren't previously available. This shows up, for example, if you rewrite with a + 0 = a in the goal (a + 0) + 0 = a; rewrite H leaves the goal a + 0 = 0.